Making it personal: performance-based assessments, ubiquitous technology, and advanced learners - Arispe, Kelly; Burston, Jack (My University, 2017)
This pedagogical implementation study advocates for performance-driven assessments to help learners become aware of and improve upon presentational speaking skills at the advanced level. A social media content creation tool, Adobe Spark Video, enabled learners to practice oral skills outside of class. The task design, implementation, and evaluation met the principle objectives of learner autonomy-namely awareness, choice, reflection, and goal setting. A step-by-step guide with examples and survey results about student perceptions is included. While the case study targeted upper-division Spanish majors, the pedagogical model could be adapted for intermediate and advanced learners of any second or foreign language.
Keywords: Instructional design; Learner autonomy; Ubiquitous learning and teaching